Comparative genomic analysis and characteristics of NCCP15740, the major type of enterotoxigenic Escherichia coli in Korea - Taesoo Kwon; Si-yun Chung; Young-Hee Jung; Su-Jin Jung; Sang-Gyun Roh; Je-Seop Park; Cheorl-Ho Kim; Won Kim; Young-Seok Bak; Seung-Hak Cho (Gut Pathogens, 2017)
Abstract Background Enterotoxigenic Escherichia coli (ETEC) cause infectious diarrhea and diarrheal death. However, the genetic properties of pathogenic strains vary spatially and temporally, making prevention and treatment difficult. In this study, the genomic features of the major type of ETEC in Korea from 2003 to 2011 were examined by whole-genome sequencing of strain NCCP15740, and a comparative genomic analysis was performed with O6 reference strains. Results The assembled genome size of NCCP15740 was 4,795,873 bp with 50.54% G+C content. Using rapid annotation using subsystem technology analysis, we predicted 4492 ORFs and 17 RNA genes. NCCP15740 was investigated for enterotoxin genes, colonization factor (CF) genes, serotype, multilocus sequence typing (MLST) profiles, and classical and nonclassical virulence factors. NCCP15740 belonged to the O6:H16 serotype and possessed enterotoxin genes encoding heat-stable toxin (STh) and heat-labile toxin (LT); 87.5% of the O6 serotype strains possessed both toxin types. NCCP15740 carried the colonization factors CS2 and CS3, whereas most O6 strains carried CS2-CS3-CS21 (79.2%). NCCP15740 harbored fewer virulence factors (59.4%) than the average observed in other O6 strains (62.0%). Interestingly, NCCP15740 did not harbor any nonclassical virulence genes. Conclusions The major type of ETEC in Korea had the same MLST sequence type as that of isolates from the USA obtained in 2011 and 2014, but had different colonization factor types and virulence profiles. These results provide important information for the development of an ETEC vaccine candidate.